Biodiversity of bivalves in the mangrove ecosystem in Kampung Jawa, Banda Aceh. Issue 1 (February 2021) - Ramadhaniaty, M; Syawali,; Karina, S; Muhammadar,
Abstract: Mangrove ecosystem as a feeding ground contributes to habitat complexity and diversity of the macrofauna, while bivalves are dominant in this ecosystem. The diversity of Bivalve had influenced by habitat conditions that have an impact on ecosystem stability. This research purposed to assess diversity and species abundance of bivalve in Kampung Jawa. The parameters analyzing included density, diversity index, and the species of a dominant index. The research was conducted in March 2020 at five stations with purposive sampling method. There are 8 species of Bivalve found in this area. The Bivalve species found are Nucula sulcata, Anadara granos, Glycymeris Modesta, Anadara transversa, Brachidontes granulatus, Anadara nodifera, Cucullaea Labiatae, and Glycymeris glycymeris . The analysis showed that Anadara transverse species was the most abundant with a density value 5.2 ind/m 2 . Diversity values from the five stations have obtained at 0.69 - 1.37 with a medium diversity category indicated that the variation of Bivalve species is quite diverse.